Economic Dimensions of Security in Central Asia - Mahnovski, Sergej (RAND Corporation, 2007)
This report assesses the economic dimensions of security in Central Asia, and considers their implications for the role of the United States. Economic development will be crucial to the future of Central Asia and broader U.S. interests in the region. However, it is unclear whether the states in the region have the institutional capacity to implement domestic reform. As the United States clarifies its long-term military relationships and commitments in the region, it should consider the region's economic development itself as a long-term security concern.